Leadership Model in Da'wah Institutions - Shiddieqy, Muhammad Dicky Hasbi Ash; Castrawijaya, Cecep (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
Leadership is someone who can influence, encourage, invite, guide, move others to receive the influence of something that can help achieve certain goals. In the era of technological development and progress, the role of institutions is needed to help a community group or organization that facilitates coordination among its members with the hope that everyone can work together or relate to one another to achieve the desired common goals. The purpose of this research is to identify leadership models in da'wah institutions. This study uses library research methods with a qualitative research approach. Sources of data in this study used books, journals and articles or writings related to leadership models in da'wah institutions.